Microbial pollution in inland recreational freshwaters of Quetta, Pakistan: an initial report. (26th February 2022) - Luqman, Muhammad; Awan, Muhammad Umer Farooq; Muhammad, Sohaib; Daud, Shakeela; Yousafzai, Asma; Arooj, Fariha
Abstract: Parasitic contamination of surface waters, especially recreational waters, is a serious problem for under-developed nations like Pakistan, where numerous outbreaks of parasitic diseases are reported each year. In the current study, parasitic presence in two surface waters (Hanna Lake and Wali-Tangi Dam) of Quetta was monitored quarterly for 1 year. The methodology involved the pre-concentration of the water samples and the subsequent preparation for the microscopic search of parasites. Physico-chemical and bacteriological variables were also studied. Wet staining, modified Trichrome staining, and modified acid-fast staining methods were used to identify various parasitic forms (cysts, oocysts, eggs, trophozoites). Collectively 11 parasitic elements (10 in Lake and 8 in Dam) belonging to 10 species were recorded, many of which are potential human pathogens. The species identified include Trichomonas sp., Isospora sp., Balantidium coli, Cryptosporidium sp., Entamoeba spp., amoebas, Microsporidium sp., Endolimax nana, Ascaris lumbricoides, and Giardia spp. Parasitic contamination remained persistent in both locations throughout the year independent of physico-chemical parameters (temperature, EC, pH, turbidity, and DO) and bacterial concentration of water. Reliance on bacterial presence for monitoring of recreational waters can be a risk for tourists. Entamoeba spp. and A. lumbricoides may be used for surface water monitoring in these waters. HIGHLIGHTS: Initial report on parasitic pollution in surface recreational waters in Pakistan. Parasitic pollution is highly persistent in both recreational waters. Reliance on bacterial parameters only for recreational waters can be risky. Entamoeba and Ascaris lumbricoides are potential candidate species for monitoring. Graphical Abstract